2017
DOI: 10.18632/oncotarget.20274
|View full text |Cite
|
Sign up to set email alerts
|

Potential therapeutic targets of triple-negative breast cancer based on its intrinsic subtype

Abstract: Triple-negative breast cancer (TNBC) is an aggressive subgroup of human breast cancer, which is characterized as estrogen receptor (ER) negative, progesterone receptor (PR) negative, and human epidermal growth factor receptor 2 (HER2) negative. TNBC is the most difficult breast cancer subgroup to treat, due to its unresponsiveness to current clinical targeted therapies, high rate of recurrence, and poor prognosis. Thus, there is an urgent medical need to identify therapeutic targets and develop more effective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
55
0
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 125 publications
(133 reference statements)
0
55
0
1
Order By: Relevance
“…TNBCs are histologically heterogeneous; the literature has repeatedly shown that TNBCs are heterogeneous in nature and understanding this characteristic has crucial clinical implications. Recent studies have identified six unique molecular subtypes, with important prognostic and predictive significance, which are potential targets for systemic therapy 27. Apart from the predominant invasive ductal carcinoma, TNBCs include metaplastic, medullary, apocrine, adenoid cystic, and invasive lobular carcinomas 6…”
Section: Discussionmentioning
confidence: 99%
“…TNBCs are histologically heterogeneous; the literature has repeatedly shown that TNBCs are heterogeneous in nature and understanding this characteristic has crucial clinical implications. Recent studies have identified six unique molecular subtypes, with important prognostic and predictive significance, which are potential targets for systemic therapy 27. Apart from the predominant invasive ductal carcinoma, TNBCs include metaplastic, medullary, apocrine, adenoid cystic, and invasive lobular carcinomas 6…”
Section: Discussionmentioning
confidence: 99%
“…There are currently no targeted treatments for TNBC, and this disease remains a major challenge for oncologists. Alternative treatments are therefore needed, to bypass chemoresistance and to improve the survival of TNBC patients …”
Section: Introductionmentioning
confidence: 99%
“…Alternative treatments are therefore needed, to bypass chemoresistance and to improve the survival of TNBC patients. 4,5,[8][9][10][11][12] Low-density lipoprotein (LDL) receptor-related protein 8 (LRP8), also known as apolipoprotein E receptor-2 (APOER2), belongs to a superfamily of single-pass transmembrane receptors comprising LDL receptors (LDLR) and LDLR-related proteins (LRPs). 13,14 LRP8 displays high levels of sequence identity (50% in for the amino acid sequence) with the very-low-density lipoprotein receptor (VLDLR).…”
mentioning
confidence: 99%
“…Over the past decades, several monoclonal antibodies and small‐molecule inhibitors have been identified and their efficacy has been evaluated for whether they are useful in improving growth, survival, angiogenesis and metastasis. Thus, some of them have been reported to be effective in improving the survival and treatment outcomes in patients with BC …”
mentioning
confidence: 99%
“…Thus, some of them have been reported to be effective in improving the survival and treatment outcomes in patients with BC. 7,8 To date, monoclonal antibodies (MABs) against epidermal growth factor receptor 2 (HER2) or vascular endothelial growth factor (VEGF), selective reversible inhibitors of HER1 and HER2, tyrosine kinases (e.g., Src), insulin-like growth factor (IGF)/IGF-receptor (IGFR), PI3K/AKT/mTOR inhibitors, RAS/ MEK/ERK inhibitors; Poly ADP ribose polymerase (PARP) inhibitors and MMP inhibitors have been developed as targeted treatment regimens for patients with BC. [9][10][11] As described here, targeted treatment regimens include agents that target growth, invasion, metastasis, angiogenesis and other key signaling pathways involved in tumorigenesis of the BC.…”
mentioning
confidence: 99%